Italian/American Short Films and Music Videos : a Semiotic Reading. - Tamburri, Anthony Julian (Purdue University Press, AtlasBooks Distribution [distributor], 2002)
Annotation This book constitutes a first look at the little-known phenomenon of the Italian/American short film. What becomes apparent is the conspicuous interest these members of the newer generation of Italian/American filmmakers exhibit vis-a-vis their ethnicity, be such films a fiction, a documentary, or a music video. Equally significant is the lens through which they see their Italian/American heritage. While the older generations concentrated more on the by now well-known thematics of immigration and organized crime, as well as the debunking thereof, these younger artists/performers of short films have added to the general theme of heritage, at various degrees, that of race, gender, and sexuality. Anthony Julian Tamburri is a professor of Italian at Florida Atlantic University, where he is also chair of the Department of Languages and Linguistics. He is the author of seven other books, including A Semiotic of Ethnicity: In (Re)cognition of the Italian/American Writer and To Hyphenate or Not to Hypenate: The Italian/American Writer: Or, An Other American? and is editor or co-editor of twelve collections, including the best-selling anthology From the Margin (1991/2000) and Screening Ethnicity (2002). He is a co-founding editor of Voices in Italian Americana: A Literary and Cultural Review.